2016
DOI: 10.1002/jcu.22363
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis: Correlation with doppler sonography of testicular arteries and sperm function

Abstract: Prevalence of testicular microlithiasis of 5.3% in Jordanian patients is similar to what has been reported in the literature. Testicular microlithiasis does not have a significant effect on Doppler parameters of testicular arteries. The apparent impairment of sperm function in patients with testicular microlithiasis warrants further studies. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:474-479, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…By pooling the data, the overall prevalence of TM was 6.0 and 4.8% in infertile and fertile men, respectively (P<0.05) [30] . On the contrary, Mahafza et al [31] revealed that 20.7% (11/53) of patients with US diagnosis of TM had associated varicocele. However, Yee et al [10] found that 6% of 1439 patients who underwent scrotal US had TM, but the incidence of TM in patients with varicocele was 9.8%.…”
Section: Discussionmentioning
confidence: 94%
“…By pooling the data, the overall prevalence of TM was 6.0 and 4.8% in infertile and fertile men, respectively (P<0.05) [30] . On the contrary, Mahafza et al [31] revealed that 20.7% (11/53) of patients with US diagnosis of TM had associated varicocele. However, Yee et al [10] found that 6% of 1439 patients who underwent scrotal US had TM, but the incidence of TM in patients with varicocele was 9.8%.…”
Section: Discussionmentioning
confidence: 94%
“…6 Some studies have found that these intrascrotal calculi lead to a decline in sperm parameters. 7,8 Other studies also revealed that these interesting things were closely related to testicular tumors. 9 However, due to the low incidence of intrascrotal calculi and the lack of relevant literature, the impact of intrascrotal calculi on sperm is unclear.…”
Section: Introductionmentioning
confidence: 94%
“… Microlithiasis is associated with abnormal semen parameters but direct causation cannot be proven[ 36 ] Testicular self-examination must be taught and encouraged in patients with microlithiasis (moderate recommendation) …”
Section: Guideline Statementsmentioning
confidence: 99%
“…Microlithiasis is associated with abnormal semen parameters but direct causation cannot be proven[ 36 ]…”
Section: Guideline Statementsmentioning
confidence: 99%